Community-Based Tourism Potential Development Strategy in Banjarmasin City: SWOT Analysis in Supporting Sustainable Tourism - Ayu Rizky Amanda; Muhammad Efendi; Rosalina Kumalawati; Rusdiansyah (Takaza Innovatix Labs Ltd., 2026)
The Banua Anyar area is one of the unique river-based culinary tourism icons in Banjarmasin, offering the experience of enjoying local traditional cuisine along the riverside, which reflects the cultural identity of the local community. This potential makes Banua Anyar an attractive destination for local-based tourism development. This study aims to identify the potential and formulate development strategies for community-based culinary tourism in the Banua Anyar area, Banjarmasin City. The area offers distinctive appeal through the diversity of traditional Banjar culinary products, supported by its strategic location along the Martapura River, making it a promising tourist destination. As a rapidly developing area, Banua Anyar holds strategic urgency to be developed as a new tourism icon of Banjarmasin City, not only to enhance regional competitiveness but also to strengthen local identity rooted in river-based culture. The results indicate that Banua Anyar has a dominant strength in the uniqueness of Banjar traditional cuisine integrated with the river environment, supported by its strategic location, which creates an authentic tourism experience and serves as the main attraction for visitors. However, the area still faces several weaknesses, particularly in terms of limited digital promotion, suboptimal spatial arrangement, and inadequate supporting facilities. Based on the SWOT analysis, the most appropriate strategy is the Growth Oriented Strategy (SO Strategy), which focuses on utilizing strengths to capture opportunities through strengthening destination branding, enhancing digital promotion, and developing community-based facilities. By implementing this strategy, Banua Anyar is expected to develop into a sustainable community-based culinary tourism destination and contribute to improving the economic welfare of the local community.